Modification of Activated Carbon from Rice Husk using Hexadecyltrimethylammonium Bromide (HDTMA-Br) Surfactant and ZnCl2 activator and Microwaves for Nitrate Ion Adsorption - Yeni Aprilia; Arnelli Arnelli; Yayuk Astuti (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Surfactant Modified Activated Carbon (SMAC) is a surfactant-modified activated carbon product. The surfactant used in this study was the cationic surfactant Hexadecyltrimethylammonium Bromide (HDTMA-Br). These surfactants can change the activated carbon's surface to be positively charged due to the presence of the surfactant hydrophilic groups. This SMAC is more selective in absorbing anions, which in this study is for the adsorption of nitrate anions. This research aims to prepare a new material that is superior to activated carbon in absorbing nitrate anions. This research was conducted in several stages. In the first stage, rice husk was carbonized through pyrolysis at 300°C for 10 minutes. In the second stage, carbon was activated using 30% ZnCl2 and microwaves for 5 minutes and 400 W. The third stage was modifying activated carbon by contacting or adsorbing HDTMA-Br on activated carbon. The concentration of HDTMA-Br varied at 200-400 ppm and the adsorption time was 3-7 hours. The success of the modification was measured by the efficiency of HDTMA-Br in modifying activated carbon. This is supported by the results of the characterization of FTIR, GSA, SEM, and thermodynamic parameters. The resulting SMAC was applied for the adsorption of nitrate anions, and the results were compared to carbon and activated carbon. The results indicate that the best SMAC is formed at an optimum concentration of 300 ppm, within 4 hours, with an adsorption efficiency of 97.345%. The characterization results also show that SMAC has been formed, as evidenced by the presence of a peak at a wavenumber of about 1500 cm-1, a C-N group derived from N(CH3)3 in the HDTMA-Br surfactant structure. The SMAC spectra also appeared weak peaks at the wave number 2918 cm-1, which indicated the CH2-R group stretching from the HDTMA-Br surfactant. SEM image shows that HDTMA-Br has covered the pores of activated carbon. Meanwhile, the SMAC surface area is lower than that of activated carbon. Thermodynamic parameters indicate that HDTMA-Br interacts physically with activated carbon. The adsorption capacity of nitrate anion by SMAC is 3,638 mg/g, higher than carbon and activated carbon.